Implementation of English as Foreign Language Teaching during Pre- and Post-COVID-19 Pandemic: A Narrative Review - Mahmood Rahimi , (Development in Language Studies, 2024)
This study explores the implementation of English as a Foreign Language (EFL) teaching practices pre-covid and post-Covid pandemic. This paper employs a narrative review of selected articles that shed light on instructional challenges and opportunities in the transition from traditional classroom teaching to online and hands-on learning. The methodology employed in this study used the Google Scholar database to select pertinent studies with keywords within the title field, spanning the years 2019-2022. This study acknowledges the impact of the pandemic on English language teaching, highlighting the need for creative teaching methods and a hybrid of online and face-to-face learning for effectiveness. This paper also stresses the significance of ongoing support to address technical challenges and ensure a smooth learning experience for students. The findings highlight the shift from traditional EFL teaching to remote teaching post-COVID, stress challenges such as digital literacy, and limited resources. This necessitates ongoing support for educators to navigate online and blended learning, integrate technology, and adapt to developing teaching methodologies.